The Change of Culture Social Post-Development of Mutiara Beach Tourism at Gumanamo Village, Mawasangka Subdistrict of Central Buton Regency - Munsir, Munsir; Dirman, La Ode; Bahtiar, Bahtiar (Universitas Halu Oleo, 2020)
Thisstudy aims to describe and analyze the condition of culture social before the development of the tourism and the change of culture social post-development and the impact of culture social post-development of Mutiara beach toursim at Gumanano village of Mawasangka Subdistrict of Central Buton Regency. The theory used in this study is the mindset of John W. Bennet (2005) about cultural adaptation. The method used is descriptive-qualitative method, namely the gained data were taken through observation, interview, and doing observation about related cases concerning the change of culture social post-development of Mutiara beach tourism.The result of the study showed that: (1) The condition culture social before the tourism: (i) cooperation system (pokaowa), (ii) belief system, (iii) the granting of the property ground,and (iv) interaction. (2)The change of culture social post-development of Mutiara beach tourism are: (i) the change of opening the new livelihood system, (ii) the change of life style, (iii) the change of the society mindset, and (iv) the society income increases. (3) Ihe impact of the change of culture socialpost-development of Mutiara beach tourism at Gumanano village of Mawasangka Subdistrict of Central Buton Regency consist of two impact, they are positive and negative impacts. The positive impact are (i) increasing the village economic turnover, and (ii) getting new knowledge. Meanwhile the negative impact are: (i) causing new culture, and (ii) adaptation with the new habit post-development of the toursim.Key words:The chnage, tourism, social-culture, Gumanano.